ANALISIS KUALITAS PERAIRAN KABUPATEN CIREBON PROVINSI JAWA BARAT - Amalia Zahroh; Etty Riani; Syaiful Anwar (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Abstract. Cirebon regency is one of the regencies supplying marine products in West Java Province. However, there are now many issues concerning the degradation of the quality of the waters that are sourced from community activities that dump their waste into the waters. This study aims to determine the quality of waters (water and sediments) of Cirebon Regency in terms of physical and chemical parameters. The method used in this study is quantitative descriptive analysis using primary data and secondary data designed to describe the physical and chemical conditions of the waters. For the status of pollutants using the STORET method. The results showed that the measurement of physical and chemical condition of waters TSS and BOD has exceeded the quality standard for marine biota (Kepmen-LH No. 51 Year 2004). While the results of heavy metals measurements on sediment concentrations of Pb and Cd have exceeded the CCME quality standard (Canadian Council of Ministers of Environment). The pollutant status of Cirebon Regency is categorized as sterile until polluted fallow.